2016
DOI: 10.3390/nu8040183
|View full text |Cite
|
Sign up to set email alerts
|

Potassium and Obesity/Metabolic Syndrome: A Systematic Review and Meta-Analysis of the Epidemiological Evidence

Abstract: The objective of this study was to investigate the associations between potassium and obesity/metabolic syndrome. We identified eight relevant studies and applied meta-analysis, and nonlinear dose-response analysis to obtain the available evidence. The results of the pooled analysis and systematic review indicated that high potassium intake could not reduce the risk of obesity (pooled OR = 0.78; 95% CI: 0.61–1.01), while serum potassium and urinary sodium-to-potassium ratio was associated with obesity. Potassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 37 publications
2
67
0
Order By: Relevance
“…People who eat more vegetables and fruits had a lower risk of developing metabolic syndrome, while fruits and vegetables were the main source of potassium intake (Aune et al, 2017). A meta-analysis demonstrated a protective effect of adequate potassium intake on obesity and metabolic syndrome (Cai et al, 2016). It is possible that potassium can affect carbohydrate accumulation and glucose homeostasis (Mariosa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…People who eat more vegetables and fruits had a lower risk of developing metabolic syndrome, while fruits and vegetables were the main source of potassium intake (Aune et al, 2017). A meta-analysis demonstrated a protective effect of adequate potassium intake on obesity and metabolic syndrome (Cai et al, 2016). It is possible that potassium can affect carbohydrate accumulation and glucose homeostasis (Mariosa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that globally, 1.65 million annual deaths related to CVD were attributed to inadequate sodium intake [ 72 ]. In contrast, potassium per se has been not univocally reported as beneficial for health [ 73 ], while sodium-to-potassium ratio has been suggested as a potential marker for metabolic risk disorders [ 74 , 75 , 76 ]. A major dietary source of sodium has been commonly reported to be “added salt” and processed meat [ 77 ], but in this sample we found that the main contributor of sodium intake was grains.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of low K on metabolic disorders is mediated partly by the decrease of nitric oxide level and deterioration of endothelial function (30) , which may cause hyperglycaemia and insulin resistance (31) . Previous studies have examined the association of Na or K intake alone with the MetS, although the results had been controversial (17,(20)(21)(22)32) . Rodrigues et al (21) found that no differences were observed in urinary Na excretion in normotensive individuals, regardless of the presence of MetS.…”
Section: Discussionmentioning
confidence: 99%